5.7.10 Problems 901 to 1000

Table 5.581: Solved using series method

#

ODE

Mathematica

Maple

6817

\[ {}x^{3} \left (x^{2}+1\right ) y^{\prime \prime \prime }-\left (4 x^{2}+2\right ) x^{2} y^{\prime \prime }+\left (10 x^{2}+4\right ) x y^{\prime }-\left (12 x^{2}+4\right ) y = 0 \]

6818

\[ {}2 \left (2-x \right ) x^{2} y^{\prime \prime }-x \left (4-x \right ) y^{\prime }+\left (3-x \right ) y = 0 \]

6819

\[ {}x^{2} \left (1-x \right ) y^{\prime \prime }+\left (5 x -4\right ) x y^{\prime }+\left (6-9 x \right ) y = 0 \]

6820

\[ {}x y^{\prime \prime }+\left (4 x^{2}+1\right ) y^{\prime }+4 x \left (x^{2}+1\right ) y = 0 \]

6821

\[ {}x^{2} y^{\prime \prime }+4 \left (x +a \right ) y = 0 \]

6822

\[ {}x y^{\prime \prime }+\left (x^{3}+1\right ) y^{\prime }+b x y = 0 \]

6823

\[ {}\left (x -1\right ) \left (x -2\right ) y^{\prime \prime }+\left (4 x -6\right ) y^{\prime }+2 y = 0 \]

6824

\[ {}y^{\prime \prime }-2 x y^{\prime }+8 y = 0 \]

6825

\[ {}y^{\prime \prime }-2 x y^{\prime }+8 y = 0 \]

6826

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+12 y = 0 \]

6827

\[ {}y^{\prime \prime } = \left (x -1\right ) y \]

6828

\[ {}x \left (x +2\right ) y^{\prime \prime }+2 \left (1+x \right ) y^{\prime }-2 y = 0 \]

6829

\[ {}x y^{\prime \prime }+y = 0 \]

6830

\[ {}y^{\prime \prime }+\left ({\mathrm e}^{x}-1\right ) y = 0 \]

6831

\[ {}x \left (1-x \right ) y^{\prime \prime }-3 x y^{\prime }-y = 0 \]

6832

\[ {}2 x y^{\prime \prime }-y^{\prime }+x^{2} y = 0 \]

6833

\[ {}\sin \left (x \right ) y^{\prime \prime }-2 \cos \left (x \right ) y^{\prime }-y \sin \left (x \right ) = 0 \]

6834

\[ {}y^{\prime \prime }-x^{2} y = 0 \]

6835

\[ {}x \left (x +2\right ) y^{\prime \prime }+\left (1+x \right ) y^{\prime }-4 y = 0 \]

6836

\[ {}x y^{\prime \prime }+\left (\frac {1}{2}-x \right ) y^{\prime }-y = 0 \]

6837

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}+\frac {1}{4}\right ) y = 0 \]

6838

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}+\frac {9}{4}\right ) y = 0 \]

6839

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}+\frac {25}{4}\right ) y = 0 \]

6840

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

6841

\[ {}y^{\prime }+x y = \cos \left (x \right ) \]

6843

\[ {}x^{3} y^{\prime \prime }+y = \frac {1}{x^{4}} \]

6844

\[ {}x y^{\prime \prime }-2 y^{\prime }+y = \cos \left (x \right ) \]

6845

\[ {}y^{\prime }-\frac {y}{x} = \cos \left (x \right ) \]

6846

\[ {}y^{\prime \prime }+y = 0 \]

6847

\[ {}y^{\prime \prime }+4 x y = 0 \]

6848

\[ {}y^{\prime \prime }-x y = 0 \]

6849

\[ {}y^{\prime \prime }+x^{2} y = 0 \]

6850

\[ {}y^{\prime }-x y = 0 \]

6851

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+p^{2} y = 0 \]

6852

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

6853

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+y = 0 \]

6854

\[ {}x y^{\prime \prime }+y = 0 \]

6855

\[ {}y^{\prime \prime }+2 x^{3} y = 0 \]

6856

\[ {}y^{\prime \prime }-x y = \frac {1}{1-x} \]

6857

\[ {}x^{2} y^{\prime \prime }-y = 0 \]

6858

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (1+x \right ) y = 0 \]

6859

\[ {}x^{2} y^{\prime \prime }-y = 0 \]

6860

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x}-x y = 0 \]

6861

\[ {}2 x y^{\prime \prime }+y^{\prime }-x^{2} y = 0 \]

6862

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }-y = 0 \]

6863

\[ {}x^{2} \left (x^{2}+1\right ) y^{\prime \prime }+x y = 0 \]

6864

\[ {}x^{2} y^{\prime \prime }+y^{\prime }+y = 0 \]

6865

\[ {}x y^{\prime \prime }+x^{3} y^{\prime }+y = 0 \]

6866

\[ {}x y^{\prime \prime }+x y^{\prime }-y \,{\mathrm e}^{x} = 0 \]

6867

\[ {}x^{2} y^{\prime \prime }+x^{2} y^{\prime }+x^{2} y = 0 \]

6868

\[ {}y^{\prime \prime }+y = 0 \]

6869

\[ {}x^{3} y^{\prime \prime }+\left (1+x \right ) y = 0 \]

6870

\[ {}x y^{\prime \prime }+x^{5} y^{\prime }+y = 0 \]

6871

\[ {}\sin \left (x \right ) y^{\prime \prime }-y = 0 \]

6872

\[ {}\cos \left (x \right ) y^{\prime \prime }-y \sin \left (x \right ) = 0 \]

6873

\[ {}x^{2} y^{\prime \prime }-y = 0 \]

6874

\[ {}x^{2} y^{\prime \prime }+\left (x -\frac {3}{4}\right ) y = 0 \]

6875

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

7201

\[ {}\left (x^{2}-25\right ) y^{\prime \prime }+2 x y^{\prime }+y = 0 \]

7202

\[ {}\left (x^{2}-25\right ) y^{\prime \prime }+2 x y^{\prime }+y = 0 \]

7203

\[ {}\left (x^{2}-2 x +10\right ) y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

7204

\[ {}\left (x^{2}-2 x +10\right ) y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

7205

\[ {}y^{\prime \prime }-x y = 0 \]

7206

\[ {}y^{\prime \prime }+x^{2} y = 0 \]

7207

\[ {}y^{\prime \prime }-2 x y^{\prime }+y = 0 \]

7208

\[ {}y^{\prime \prime }-x y^{\prime }+2 y = 0 \]

7209

\[ {}y^{\prime \prime }+x^{2} y^{\prime }+x y = 0 \]

7210

\[ {}y^{\prime \prime }+2 x y^{\prime }+2 y = 0 \]

7211

\[ {}\left (x -1\right ) y^{\prime \prime }+y^{\prime } = 0 \]

7212

\[ {}\left (x +2\right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

7213

\[ {}y^{\prime \prime }-\left (1+x \right ) y^{\prime }-y = 0 \]

7214

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-6 y = 0 \]

7215

\[ {}\left (x^{2}+2\right ) y^{\prime \prime }+3 x y^{\prime }-y = 0 \]

7216

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

7217

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

7218

\[ {}\left (1+x \right ) y^{\prime \prime }-\left (2-x \right ) y^{\prime }+y = 0 \]

7219

\[ {}y^{\prime \prime }-2 x y^{\prime }+8 y = 0 \]

7220

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime } = 0 \]

7221

\[ {}y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

7222

\[ {}y^{\prime \prime }+{\mathrm e}^{x} y^{\prime }-y = 0 \]

7223

\[ {}y^{\prime \prime }+x y^{\prime }+y = 0 \]

7224

\[ {}x^{3} y^{\prime \prime }+4 x^{2} y^{\prime }+3 y = 0 \]

7225

\[ {}x \left (x +3\right )^{2} y^{\prime \prime }-y = 0 \]

7226

\[ {}\left (x^{2}-9\right )^{2} y^{\prime \prime }+\left (x +3\right ) y^{\prime }+2 y = 0 \]

7227

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}+\frac {y}{\left (x -1\right )^{3}} = 0 \]

7228

\[ {}\left (x^{3}+4 x \right ) y^{\prime \prime }-2 x y^{\prime }+6 y = 0 \]

7229

\[ {}x^{2} \left (x -5\right )^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}-25\right ) y = 0 \]

7230

\[ {}\left (x^{2}+x -6\right ) y^{\prime \prime }+\left (x +3\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

7231

\[ {}x \left (x^{2}+1\right )^{2} y^{\prime \prime }+y = 0 \]

7232

\[ {}x^{3} \left (x^{2}-25\right ) \left (x -2\right )^{2} y^{\prime \prime }+3 x \left (x -2\right ) y^{\prime }+7 \left (5+x \right ) y = 0 \]

7233

\[ {}\left (x^{3}-2 x^{2}+3 x \right )^{2} y^{\prime \prime }+x \left (x -3\right )^{2} y^{\prime }-\left (1+x \right ) y = 0 \]

7234

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+5 \left (1+x \right ) y^{\prime }+\left (x^{2}-x \right ) y = 0 \]

7235

\[ {}x y^{\prime \prime }+\left (x +3\right ) y^{\prime }+7 x^{2} y = 0 \]

7236

\[ {}x^{2} y^{\prime \prime }+\left (\frac {5}{3} x +x^{2}\right ) y^{\prime }-\frac {y}{3} = 0 \]

7237

\[ {}x y^{\prime \prime }+y^{\prime }+10 y = 0 \]

7238

\[ {}2 x y^{\prime \prime }-y^{\prime }+2 y = 0 \]

7239

\[ {}2 x y^{\prime \prime }+5 y^{\prime }+x y = 0 \]

7240

\[ {}4 x y^{\prime \prime }+\frac {y^{\prime }}{2}+y = 0 \]

7241

\[ {}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

7242

\[ {}3 x y^{\prime \prime }+\left (2-x \right ) y^{\prime }-y = 0 \]